Images of Previous Mothers through Health Education, Additional Food Package Materials and Community Empowerment in Sucopangepok Village District of Jelbuk-Jember - Lantin Sulistyorini (Faculty of Medicine, University of Jember, 2018)
The period of pregnancy greatly determines the quality of human resources of the future, because the condition of the fetus in the womb determines the growth of children. Factors that affect maternal health is the mother's nutritional condition. The research design is descriptive. The sampling technique uses total sampling. The sample size of trimester II and III pregnant women were 58 respondents. Univariate data analysis. The result of analysis indicated that pregnant women were mostly at risk of chronic energy deficiency (79.3%), pregnant woman's knowledge level about fulfillment of nutritional requirement during pregnancy after health education mostly categorized good (51.7%), knowledge level of posyandu cadre the fulfillment of nutritional needs of pregnant women before and after health education is mostly categorized good (51.9% and 74.0%). The attitude of posyandu cadre in fulfillment of the nutritional requirement of the pregnant mother before and after health education mostly categorized good (66.7% and 74.0%). Motivation of posyandu cadres in maintaining the nutrition of pregnant women after the treatment was mostly good (70.4%), the weight of pregnant women before and after local-based supplementary feeding showed increased weight according to gestational age (79.3% and 91.4%). The results showed most of the pregnant women have normal nutritional status with arm circumference size ≥23.5 cm. Suggestions for pregnant women to keep their nutritional status normal by maintaining diet and always carrying out routine atenatal care visits and health workers providing supplementary feeding to pregnant women with chronic energy shortages. Keywords: Maternal care movement, additional food package, nutritional status